Exposure to Ambient Particulate Matter Is Associated With Accelerated Functional Decline in Idiopathic Pulmonary Fibrosis - Winterbottom, Christopher J; Shah, Rupal J; Patterson, Karen C; Kreider, Maryl E; Panettieri, Jr, Reynold A; Rivera-Lebron, Belinda; Miller, Wallace T; Litzky, Leslie A; Penning, Trevor M; Heinlen, Krista; Jackson, Tara; Localio, A Russell; et al. (Chest, 2018)
Idiopathic pulmonary fibrosis (IPF), a progressive disease with an unknown pathogenesis, may be due in part to an abnormal response to injurious stimuli by alveolar epithelial cells. Air pollution and particulate inhalation of matter evoke a wide variety of pulmonary and systemic inflammatory diseases. We therefore hypothesized that increased average ambient particulate matter (PM) concentrations would be associated with an accelerated rate of decline in FVC in IPF. We identified a cohort of subjects seen at a single university referral center from 2007 to 2013. Average concentrations of particulate matter < 10 and < 2.5 μg/m (PM and PM , respectively) were assigned to each patient based on geocoded residential addresses. A linear multivariable mixed-effects model determined the association between the rate of decline in FVC and average PM concentration, controlling for baseline FVC at first measurement and other covariates. One hundred thirty-five subjects were included in the final analysis after exclusion of subjects missing repeated spirometry measurements and those for whom exposure data were not available. There was a significant association between PM levels and the rate of decline in FVC during the study period, with each μg/m increase in PM corresponding with an additional 46 cc/y decline in FVC (P = .008). Ambient air pollution, as measured by average PM concentration, is associated with an increase in the rate of decline of FVC in IPF, suggesting a potential mechanistic role for air pollution in the progression of disease.